Analyzing the Role of Receptor Internalization in the Regulation of Melanin-Concentrating Hormone Signaling. (17th November 2013) - Moden, Jay I.; Haude, Katrina; Carroll, Robert; Goodspeed, Andrew; Cook, Laurie B.
Abstract : The regulation of appetite is complex, though our understanding of the process is improving. The potential role for the melanin-concentrating hormone (MCH) signaling pathway in the treatment of obesity is being explored by many. It was hypothesized that internalization of MCH receptors would act to potently desensitize cells to MCH. Despite potent desensitization of ERK signaling by MCH in BHK-570 cells, we were unable to observe MCH-mediated internalization of MCH receptor 1 (MCHR1) by fluorescence microscopy. A more quantitative approach using a cell-based ELISA indicated only 15% of receptors internalized, which is much lower than that reported in the literature. When β -arrestins were overexpressed in our system, removal of receptors from the cell surface was facilitated and signaling to a leptin promoter was diminished, suggesting that internalization of MCHR1 is sensitive to cellular β -arrestin levels. A dominant-negative GRK construct completely inhibited loss of receptors from the cell surface in response to MCH, suggesting that the internalization observed is phosphorylation-dependent. Since desensitization of MCH-mediated ERK signaling did not correlate with significant loss of MCHR1 from the cell surface, we hypothesize that in this model system regulation of MCH signaling may be the result of segregation of receptors from signaling components at the plasma membrane.